Effect of an intervention of exercise on sleep and seizure frequency in idiopathic epileptic dogs. (11th November 2022) - Grady, K.; Cameron, S.; Kent, S. P.; Barnes Heller, H.; Barry, M. M.
Abstract : Objective: The goal of this study was to compare sleep and seizure frequency between epileptic dogs prescribed a 20% activity increase and epileptic dogs not prescribed an activity increase. Methods: Sixty‐nine dogs receiving anti‐epileptic drug therapy were enrolled in a 6‐month prospective, randomised, placebo‐controlled clinical trial with an intention‐to‐treat analysis. A canine activity monitoring device was used to measure activity levels and sleep scores. Results: Using an intention‐to‐treat analysis, the treatment group had an average of 0.381 more seizures per month (95% CI: 0.09 to 0.68) compared with the control group, although the difference in seizure days per month was not statistically significant. In a subgroup analysis of dogs whose activity increased by at least 10%, partial compliers had 0.719 more seizures per month (95% CI: 0.22 to 1.22) and 0.581 seizure days per month (95% CI: 0.001 to 1.16) compared with the control group. Sleep scores increased by 1.2% in the treatment compared with the control group (95% CI: 0.2 to 2.3%). Conclusions: Seizure frequency and sleep score increased slightly, but significantly, in dogs with idiopathic epilepsy prescribed an increase in activity, compared with a control group.